2020
DOI: 10.1007/s10560-020-00689-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sexual Orientation Bullying Victimization are Associated with Gun Carrying Among Adolescent Boys

Abstract: Gun carrying and bullying victimization are associated among adolescent boys, however the type of the bullying remains relatively unknown. This study aimed to identify whether experiencing bullying victimization based on gender and sexual orientation is associated with carrying a gun to school among adolescent boys. A cross-sectional analysis among a representative sample of high school boys (n = 3672) from the 2015 Maine Integrated Youth Health Survey was conducted. Odds ratios (OR) and 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
5
9
0
1
Order By: Relevance
“…These findings are particularly salient as they are independent of several potential confounding factors, including multiple forms of bullying victimization, avoiding school due to lack of safety, and being threatened or injured at school with a weapon. Presumably, outside the context of muscle-building exercise, these factors would increase one’s likelihood of carrying a weapon and/or engaging in physical fighting for self-protection ( Ganson & Nagata, 2020 ; Pham et al, 2017 ; Shetgiri et al, 2015 ; Van Geel et al., 2014 ). Additionally, these findings are independent of team sports participation, which would presumably account for the high engagement in muscle-building exercise (i.e., for sports-related purposes) via practices and training ( Nagata et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are particularly salient as they are independent of several potential confounding factors, including multiple forms of bullying victimization, avoiding school due to lack of safety, and being threatened or injured at school with a weapon. Presumably, outside the context of muscle-building exercise, these factors would increase one’s likelihood of carrying a weapon and/or engaging in physical fighting for self-protection ( Ganson & Nagata, 2020 ; Pham et al, 2017 ; Shetgiri et al, 2015 ; Van Geel et al., 2014 ). Additionally, these findings are independent of team sports participation, which would presumably account for the high engagement in muscle-building exercise (i.e., for sports-related purposes) via practices and training ( Nagata et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Do not count the days when you carried a gun only for hunting or for a sport, such as target shooting. )” Response options for each question were dichotomized to zero (0) days and one (1) or more days ( Ganson & Nagata, 2020 ; Jewett et al, 2021 ; Pham et al, 2017 ; Vaughn et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the GFSZA and GFSA are both federal laws, in some states, K-12 schools can permit students in possession of a permit to carry a gun [2,3]. Many studies have shown an association between being the victim of bullying and carrying a weapon, particularly a firearm [4][5][6][7]. The different manifestations of bullying have varying likelihoods of carrying firearms [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown an association between being the victim of bullying and carrying a weapon, particularly a firearm [4][5][6][7]. The different manifestations of bullying have varying likelihoods of carrying firearms [4][5][6]. It is also evident that differences in victim classes (non-victims, those who experience different types of bullying, and those who are highly victimized) may not be good predictors of the likelihood to carry a firearm [6].…”
Section: Introductionmentioning
confidence: 99%